Development of a TaqMan-based real-time PCR assay for the rapid and specific detection of pigeon torque teno virus. (June 2018) - Wan, Chunhe; Chen, Cuiteng; Cheng, Longfei; Fu, Guanghua; Shi, Shaohua; Fu, Qiuling; Liu, Rongchang; Chen, Hongmei; Huang, Yu
Abstract: Pigeon torque teno virus (PTTV), a recently discovered circular DNA virus. Here, we developed a Taq Man-based real-time PCR for rapid and specific detection of PTTV infections with sensitivity up to 49.3 copies/μl. Positive signals can be observed by the assay in pigeon embryonated eggs, which indicted that PTTV can be transmitted vertically. Our findings play important implications for a better understanding the transmission of torque teno virus in pigeons. Highlights: A TaqMan-based real-time PCR method for pigeon torque teno virus (PTTV) was developed. The method showed high sensitivity, specificity and reproducibility. PTTV can be vertically transmitted, which indicates PTTV persistent co-circulating in China.